Geotechnical Insights into Andesite Quarry Slope Stability: A Case Study from Desa Usul, Indragiri Hulu, Riau, Indonesia - Diondo Simatupang, Ismon; Kausarian, Husnul; Elizar (Journal of Geoscience, Engineering, Environment, and Technology, 2024)
This study investigates the slope stability of andesite quarries from a geotechnical and civil engineering perspective, emphasizing geological, geotechnical, and civil engineering factors influencing stability and their implications for mining and infrastructure operations. Andesite is widely used as an aggregate material in construction due to its compliance with Indonesian National Standards (SNI) for aggregate quality. Through comprehensive geotechnical assessments and slope stability analyses, the research concludes that the Andesite quarry slopes exhibit high levels of stability, supporting safe mining practices. Calculated Factor of Safety (FS) values consistently exceed safety thresholds, indicating favorable conditions for resource extraction. Slope simulations using Slide and Geoslope applications confirm the robustness of the slopes, with Safety Factor (FS) values ranging from 1.601 to 2.614. The implementation of open-cut methods, supported by meticulous slope design and blasting techniques, enhances safety and efficiency in mining operations. The study underscores the feasibility and safety of mining activities in the researched area, contributing to the advancement of mining engineering practices in volcaniclastic environments. Effective slope management strategies are essential for ensuring sustainable resource extraction while prioritizing worker safety and environmental integrity.